Social Capital and the Quality of Government : Evidence from the United States - Knack, Stephen (World Bank, Washington, DC, 2014)
Social capital - in the form of general trust and strong civi norms that call for cooperation when large-scale collective action is needed - can improve government performance in three ways: 1) It can broaden government accountability, making government responsive to citizens at large, rather than to narrow interests. 2) It can facilitate agreement where political preferences are polarized. 3) It is associated with greater innovation when policymakers face new challenges. Consistent with these arguments, Putnam (1993) has shown that regional governments in the more trusting, more civic-minded northern, and central parts of Italy provide public services more effectively than do those in the less trusting, less civic-minded southern regions. Using cross-country data, La Porta and others (1997), and Knack and Keefer (1997), obtained findings consistent with Putnam's evidence. For samples of about thirty nations (represented in the World Value Surveys), they found that societies with greater trust tended to have governments that performed significantly better. The authors used survey measures of citizen confidence in government as well as subjective indicators of bureaucratic inefficiency. The author further analyzes links between social capital and government performance, using data for the United States. In states with more social capital (as measured by an index of trust, volunteering, and census response), government performance is rated higher, based on ratings constructed by the Government Performance Project. This result is highly robust to including a variety of control variables, considering the possibility of influential outlying values, treating the performance ratings as ordinal, rather than cardinal, and correcting for possible endogeneity.